Financování regionálního školství - Půhoná, Diana (Univerzita Pardubice, 2006)
Bakalářská práce se zabývá systémem financování a strukturou regionálního školství v České republice. Obecná část je všeobecně zaměřena na regionální školství, vymezuje jeho cíle, strukturu a organizaci a podává srovnání se zeměmi OECD. Speciální část popisuje rozpis finančních prostředků na školství v Libereckém kraji.

The Bachelor work goes into the funding system and the regional educational system in the Czech republic. The general part localizes to the regional education, determines its structure, organization and purposes and provides a comparation with the OECD countries. The separate part of this work describes the financial means intended for education in the Liberec region.
Financing of regional education
Keywords: Educational system; regions; structures of education; regiony; financování; struktury školství; školství